The Impact of Electronic Banking and Information Technology on the Employees of Banking Sector. (November 2017) - Gupta, Sweety; Yadav, Anshu
In the last three decades, the banking sector has seen a profound transformation owing to the changes in the global financial environment. The major change witnessed in the banking sector has been great advances in financial innovations and technologies, which are a result of turmoil in the global financial environment. The improvement in financial innovations and technologies has made E-banking an intense part of the banking sector. E-banking has revolutionized the lives of all individuals of present times and is considered to be a wave of information revolution after the agricultural and industrial revolution. Earlier banking customers were required to personally visit a bank branch in order to transact through their saving accounts but with the arrival of Internet banking the manner in which financial transactions are carried out have changed. Although E-banking has been popular among computer literates for many years, its popularity is growing exponentially as Internet usage grows and people discover the numerous benefits that are provided by online banking. In today's increasingly integrated financial systems facing higher volatilities, more competition and higher time constraints, E-banking has become an integral part of the global financial environment in order to meet different requirements of customers of banking sector, thereby meeting the increased expectations of the participants in Indian banking system. This study makes an attempt to analyse the impact of E-banking and information technology on the employees of banking sector.